Overexpression of synuclein-γ predicts lack of benefit from radiotherapy for breast cancer patients. Issue 1 (December 2016) - Min, Li; Zhang, Cheng; Ma, Ruolan; Li, Xiaofan; Yuan, Hua; Li, Yihao; Chen, Ruxuan; Liu, Caiyun; Guo, Jianping; Qu, Like; Shou, Chengchao
Abstract Background Although radiotherapy following mastectomy was demonstrated to reduce the recurring risk and improve the prognosis of patients with breast cancer, it is also notorious for comprehensive side effects, hence only a selected group of patients can benefit. Therefore, the screening of molecular markers capable of predicting the efficacy of radiotherapy is essential. Methods We have established a cohort of 454 breast cancer cases and selected 238 patients with indications for postoperative radiotherapy. Synuclein-γ (SNCG) protein levels were assessed by immunohistochemistry, and SNCG status was retrospectively correlated with clinical features and survival in patients treated or not treated with radiotherapy. Gene Set Enrichment Analysis (GSEA) and survival analysis for online datasets were also performed for further validation. Results Among patients that received radiotherapy (82/238), those demonstrating positive SNCG expression had a 55.0 month shorter median overall survival (OS) in comparison to those demonstrating negative SNCG expression (78.4 vs. 133.4 months, log rankχ 2 = 16.13;p < 0.001). Among the patients that received no radiotherapy (156/238), SNCG status was not correlated with OS (log rankχ 2 = 2.40;p = 0.121). A COX proportional hazard analysis confirmed SNCG as an independent predictor of OS, only for patients who have received radiotherapy. Similar results were also obtained for distant metastasis-free survival (DMFS). A GSEA analysis indicated that SNCG was strongly associated with genes related to a radiation stress response. A survival analysis was performed with online databases consisting of breast cancer, lung cancer, and glioblastoma and further confirmed SNCG's significance in predicting the survival of patients that have received radiotherapy. Conclusion A positive SNCG may serve as a potential marker to identify breast cancer patients who are less likely to benefit from radiotherapy and may also be extended to other types of cancer. However, the role of SNCG in radiotherapy response still needs to be further validated in randomized controlled trials prior to being exploited in clinical practice.